EVALUATION OF THE EFFECT OF SODIUM–GLUCOSE COTRANSPORTER-2 INHIBITORS IN THE TREATMENT OF CHRONIC KIDNEY DISEASE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Yunusova Farangiz Abdulla qizi; Shagazatova Barno Habibullayevna (The Conference Hub, 2025)
Type 2 diabetes mellitus (T2DM) is one of the most widespread metabolic diseases worldwide, and one of its most severe complications is chronic kidney disease (CKD). According to various sources, 30–40% of patients with T2DM develop CKD, which significantly increases the risk of mortality and disability. Therefore, identifying new and effective treatment strategies to protect kidney function in patients with diabetes is an urgent priority.In recent years, sodium–glucose cotransporter-2 (SGLT-2) inhibitors—particularly empagliflozin—have been shown to possess not only hypoglycemic effects but also nephroprotective properties. By inducing glucosuria, they reduce blood glucose levels while simultaneously stabilizing glomerular filtration, decreasing albuminuria, and exerting anti-inflammatory effects that help protect the kidneys.